Traits of Mumineen in Qur’an: A Guide for Maneuvering Contemporary challenges - Ghani, Ms. Fakhra; Ayaz, Dr. Hafsah (Al-Amīr Research Journal for Islamic Studies, 2024)
This study delves into the significant insights that the Quran offers in comprehending the unique characteristics of Momineen, people who are known for their unshakable faith. By means of a methodical examination of complex Quranic verses, the study aims to disentangle the remarkable characteristics that characterize the Momineen. The goal is to expose the moral and spiritual aspects that, in accordance with the Quran, define the conduct and personality of individuals who represent true believers. The study aims to reveal the spiritual and moral aspects that influence the conduct and character of individuals who represent real believers in the Quran. This exploration provides a greater understanding of the virtues, values, and ethical principles that comprise the divine blueprint directing the lives of Momineen. This study fosters a comprehensive grasp of the holy relationship between religion and virtuous life by acting as a bridge between Islamic teachings and how believers manifest these teachings in their actions. Keywords: Quranic insights, Momineen, religion, traits, personality, Spiritual aspect.